Maternal and Fetal Complications of Macrosomic Pregnancies - Hawa Sardar, Zubaida Khanum, Irum Shehzadi, Beenish Salam, Shermeen Kousar, Uzma Bibi (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aimed to determine the maternal and fetal complications among patients of macrosomic pregnancies. Study Design: Descriptive/cross-sectional Place and Duration: Department of Gyne & Obs King Abdullah Teaching Hospital Mansehra/Gulnawaz Teaching Hospital Bannuduring from the period August 2022 to March 2023. Methods: 90 females diagnosed with macrosomic pregnancies were included. Gestational age and parity among females were recorded. Complications affecting both the mother and the baby are more common in pregnancies characterized by macrosomia (birth weight (BW) > 4000 g) or severe macrosomia (BW > 4500 g). The SPSS 20.0 was used for data analyzation. Results: The pregnant females had mean age of 28.19±6.81 years. The mean gestational age of the cases was 40.07±1.38 weeks. Mean parity of the females was 3.6±5.27. The most common fetal complication was shoulder dystocia in 12 (13.33%) followed by birth trauma in 7 (7.78%), perinatal asphyxia in 4 (4.44%) and low Apgar score in 4 (4.44%) patients. Most common maternal complication was perineal tear in 48 (53.33%) followed by cesarean section in 30 (33.33%) and postpartum hemorrhage in 14 (15.56%) patients respectively. Conclusion: We concluded that macrosomic pregnancies are highly associated with adverse maternal and fetal complications. Keywords: Macrosomia, Cesarean section, Perineal Tear, Shoulder Dystocia